Female sex is an independent risk factor for recurrence after ethanol Marshall bundle elimination in atrial fibrillation ablation - Chen, Hongxu; Xiong, Xiong; Chen, Dan; Li, Xi; Yang, Liheng; Liu, Zuowei; Chen, Yanhong; Zhang, Jinlin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAtrial fibrillation (AF) exhibits gender disparities in prevalence, complications, pharmacological management, and ablation efficacy. Ethanol infusion of the vein of Marshall (EIVOM) is promising for enhancing AF ablation success rate, yet sex differences of EIVOM are lacking evidence.MethodThis was a non-randomized, single-center, retrospective observational study. Patients with AF received stepwise ablations composed of EIVOM, pulmonary vein isolation, and linear ablation. The primary endpoint was defined as the recurrence of atrial tachycardia over 30 s. Propensity score matching (PSM) was performed to reduce selection bias.ResultsFrom April 2020 to May 2022, 432 patients were included, comprising 288 male patients and 144 female patients. Compared with the male patients, the female patients were older, with worse heart function class. EIVOM success rate was significantly lower in the female patients compared with the male patients (86.1% vs. 93.4%). No significant differences in major procedural complications were observed between the male and female patients. During a median follow-up of 12 months, the female patients had significantly higher AF recurrence. Multivariate Cox regression analysis showed that female sex, body mass index <21.62, left atrial diameter >47 mm, and complex fractionated atrial electrogram ablation are independent risk factors for AF recurrence. After PSM, the AF recurrence rate remained statistically higher in the female patients compared with the male patients.ConclusionCompared with the male patients, the female patients were older, more symptomatic, and had worse heart function. The female patients had significantly higher AF recurrence after EIVOM combined with catheter ablation.